Influence of Hot Air and Modified Atmosphere Packaging on Chilling Injury Incidence and Metabolism of Soluble Sugars in Eggplant Fruit (Solanum melongena L.) - Gutierrez, Diego Ricardo (2017)
In this study, the influence of hot air (HA) and passive modified atmosphere packaging (MAP) on chilling injury (CI) and the metabolism of soluble carbohydrates on eggplant fruits stored at 3 °C for 9 days were investigated. Thus, the content of soluble sugar and the activities of enzymes associated to sugar metabolism, e.g. sucrose synthase (SS-synthesis and SS-cleavage), acid invertase (AI), neutral invertase (NI) and sucrose phosphate synthase (SPS) were analyzed. The CI symptoms in the control were manifested in association with an accumulation of sucrose. The fruit treated with HA and MAP showed significantly higher sucrose content with a significantly higher SS-synthesis activity and mildest CI symptoms respect the control. Thus the treatments with HA and MAP applied were effective in reduce CI incidence in the eggplant fruit. This would be associated with the increase in sucrose content and higher activity of SS-synthesis during cold storage.